2021
DOI: 10.3390/ijms22094650
|View full text |Cite
|
Sign up to set email alerts
|

A Soluble Epoxide Hydrolase Inhibitor, 1-trifluoromethoxyphenyl-3-(1-propionylpiperidin-4-yl) Urea, Ameliorates Experimental Autoimmune Encephalomyelitis

Abstract: Polyunsaturated fatty acids (PUFAs) are essential FAs for human health. Cytochrome P450 oxygenates PUFAs to produce anti-inflammatory and pain-resolving epoxy fatty acids (EpFAs) and other oxylipins whose epoxide ring is opened by the soluble epoxide hydrolase (sEH/Ephx2), resulting in the formation of toxic and pro-inflammatory vicinal diols (dihydroxy-FAs). Pharmacological inhibition of sEH is a promising strategy for the treatment of pain, inflammation, cardiovascular diseases, and other conditions. We test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…To further determine the effects of EpOME versus DiHOME on colon tumorigenesis, we tested the extent to which inhibition of soluble epoxide hydrolase (sEH), which is a major enzyme that converts EpOME to DiHOME, 24 exacerbates colon tumorigenesis. Previous studies have shown that treatment with an sEH inhibitor TPPU increases EpOME and decreases DiHOME levels 45 . We maintained mice on the control diet, treated them with an sEH inhibitor TPPU or vehicle via drinking water, then stimulated the mice with AOM/DSS to induce colon tumorigenesis (see the scheme of the experiment in Figure S3A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further determine the effects of EpOME versus DiHOME on colon tumorigenesis, we tested the extent to which inhibition of soluble epoxide hydrolase (sEH), which is a major enzyme that converts EpOME to DiHOME, 24 exacerbates colon tumorigenesis. Previous studies have shown that treatment with an sEH inhibitor TPPU increases EpOME and decreases DiHOME levels 45 . We maintained mice on the control diet, treated them with an sEH inhibitor TPPU or vehicle via drinking water, then stimulated the mice with AOM/DSS to induce colon tumorigenesis (see the scheme of the experiment in Figure S3A).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that treatment with an sEH inhibitor TPPU increases EpOME and decreases DiHOME levels. 45 We maintained mice on the control diet, treated them with an sEH inhibitor TPPU or vehicle via drinking water, then stimulated the mice with AOM/DSS to induce colon tumorigenesis (see the scheme of the experiment in Figure S3A). We found that treatment with the sEH inhibitor increased tumor number and tumor size, enhanced colonic infiltration of immune cells, modulated the expression of inflammatory and tumorigenic genes, and increased expression of βcatenin in colon (Figure S3B-E).…”
Section: La-derived Cyp Metabolite Epome But Not Its Downstream Metab...mentioning
confidence: 99%
“…Females from the control and the experimental group were housed together in a cage. Starting at post-induction day 5 (PID5) and ending on PID 28, mice were scored daily for clinical symptoms on the established rating scale (Kihara et al, 2005 ; Jonnalagadda et al, 2021 ). Mice were weighed and scored daily for signs of progressive paralysis: 0—no abnormalities; 0.5—mild loss of tail tone; 1.0—complete loss of tail tone; 1.5—mildly abnormal gait and difficulty in righting; 2.0—abnormal gait and hindlimb weakness; 2.5—beginning hindlimb paralysis; 3.0—complete or almost complete hindlimb paralysis; 3.5—paralysis and inability to upright body; 4.0—hindlimb paralysis and forelimb weakness or paralysis; 4.5—paralysis without an attempt to move around the cage; 5.0—moribund or dead.…”
Section: Methodsmentioning
confidence: 99%
“…sEH are able to metabolize epoxyeicosatrienoic acids (EETs), which reduce inflammation and oxidative stress, by epoxide ring opening to the corresponding diols by the soluble epoxide hydrolase [ 84 ]. sEH inhibition is a promising strategy for the treatment of pain, inflammation, cardiovascular diseases, and other conditions [ 173 ].…”
Section: Tacrine Hybrids With Biological Active Organic Scaffoldsmentioning
confidence: 99%